CircRNAs modulate response of cancer cells to gemcitabine - Zahra Tajik; Soudeh Ghafouri-Fard (Advances in Cancer Biology - Metastasis)
As a chemotherapeutic agent, gemcitabine makes the backbone of several chemotherapeutic regimens, particularly those used for advanced cancers. However, drug resistance confines the long-term therapeutic impact of gemcitabine in cancer treatment and makes the patients' prognosis poor. Several mechanisms such as alteration of membrane transporters, abnormal regulation of activating and inactivating enzymes, and alterations in signaling pathway have been proposed for induction of resistance to gemcitabine. However, none of them could individually explain the varied spectrum of patients' responses to this agent. Recent recognition of the role of circular RNAs (circRNAs) in the pathoetiology of cancer has opened a new venue for identification of molecular events leading to chemoresistance. The current review provides insights into the role of specific circRNAs in determination of response to gemcitabine.